(untitled) (Academicia Globe: Inderscience Research, 2024)
This article outlines a strategic framework for the development of a project aimed at enhancing a company’s competitive advantages. In today’s dynamic business landscape, gaining a competitive edge is crucial for sustained success and growth. The article explores essential steps in project development, including thorough analysis of internal and external factors, definition of clear objectives, stakeholder engagement, development of actionable plans, implementation, and continuous monitoring and adaptation. By following this structured approach, organizations can identify opportunities for improvement, leverage their strengths, and strategically position themselves for long-term success in the marketplace.